Children in the shadow of AIDS: Studies of vulnerable children and orphans in three provinces in South Africa - Adato, Michelle; Kadiyala, Suneetha; Roopnaraine, Terry; Biermayr-Jenzano, Patricia; Norman, Amy (International Food Policy Research Institute, 2006)
With a population of almost 45 million people and an estimated 5.5 million people infected with HIV, South Africa has the largest number of individuals living with the virus in a single country. This tragedy has also brought a rising tide of orphans and vulnerable children. A 2004 analysis by UNAIDS/UNICEF/USAID estimates that, of 17 million children under age 17, 13 percent (2.2 million) are orphans. The number of orphans due to AIDS is approximately half that figure, or 1.1 million. There is a pressing need to increase our understanding of the vulnerabilities of orphans in different economic, social and cultural contexts, and the options for providing support under these conditions. Even less is known about the experience of children affected by HIV and AIDS but not yet orphaned. This paper examines the experiences of children affected by HIV and AIDS at different stages of impact, in three provinces of South Africa: Eastern Cape, Western Cape, and KwaZulu-Natal, based on in-depth interviews, observations, and survey data.